Efektivitas Kurikulum Kewirausahaan di Pendidikan Tinggi dalam Meningkatkan Kesiapan Mahasiswa sebagai Wirausahawan - Yeldy Dwi Genadi; Girsang, Zefanya Andryan; Busman, Sherwin Ary; Anwar, Adrianda; Zamroni Alpian Muhtarom (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
This study aims to evaluate the effectiveness of the entrepreneurship curriculum in higher education, particularly at the University of Mataram, in enhancing students' readiness to become entrepreneurs. The research was motivated by the high unemployment rate among university graduates and their lack of preparedness to enter the real business world. Using a quantitative approach, the study involved 200 final-year students who had completed entrepreneurship courses. The analysis revealed that components of the curriculum such as understanding of business concepts, managerial skills, business idea development, and risk-taking readiness had a significant impact on students’ entrepreneurial readiness. Among these, business idea development showed the strongest influence, followed by business concept comprehension and managerial skills. The findings also highlighted that students felt the curriculum was overly theoretical and insufficient to build practical readiness for starting a business. Therefore, the study recommends strengthening practical aspects of the curriculum, such as internships, real business projects, and industry collaboration. It concludes that entrepreneurship education in higher education institutions should be more experiential and practice-oriented to produce independent and competent graduates in the entrepreneurial field.